Employer silencing in a context of voice regulations: Case studies of non‐compliance. (20th February 2020) - Hickland, Eugene; Cullinane, Niall; Dobbins, Tony; Dundon, Tony; Donaghey, Jimmy
Abstract: This article, drawing on the latest insights into organisational silence, considers how employers seek to withhold information and circumvent meaningful workplace voice when confronted with regulatory requirements. It offers novel theoretical insights by redefining employer silencing as characterised by the withholding of information and the restriction of workplace dialogue. In outlining three principal routes of non‐compliance—avoidance, suppression, and neglect—we empirically illustrate the path to silence in the regulatory context of the European Union Directive establishing a general framework for informing and consulting employees. Rather than considering how employers utilised the regulations, as existing research considers, we look at how employers circumvented the regulatory space in three case studies in the United Kingdom and Ireland and the significant role of employer silencing as a tool for explaining this dynamic.